Cryopreservation of Human Midbrain Dopaminergic Neural Progenitor Cells Poised for Neuronal Differentiation - Drummond, Nicola J.; Singh Dolt, Karamjit; Canham, Maurice A.; Kilbride, Peter; Morris, G. John; Kunath, Tilo (Frontiers in Cell and Developmental Biology, 2020)
Human pluripotent stem cells can be differentiated into midbrain dopaminergic (mDA) neurons by directing cells through a floor plate progenitor stage. The developmental identity of mDA neurons produced using floor plate protocols is similar to substantia nigra neurons, and this has improved the ability to model Parkinson’s disease (PD) in a dish. Combined with the unlimited growth potential of pluripotent stem cells, mDA neural progenitor cell production can provide a scalable source of human dopaminergic neurons for diverse applications. However, due to the complexity and length of the protocols and inherent differences between cell lines, considerable variability of the final population of neurons is often observed. One solution to this problem is to cryopreserve committed mDA neural progenitor cells in a ready-to-use format. Creating a bank of cryopreserved mDA neural progenitor cells poised for neuronal differentiation could significantly improve reproducibility and facilitate collaborations. Here we have compared six (6) different commercial cryopreservation media and different freezing conditions for mDA neural progenitor cells differentiated from human embryonic stem cell lines. Significant differences in cell recovery were observed at 24h post-thawing, but no differences were observed immediately upon thawing. The presence of ROCK inhibitors improved cell recovery at 24h for all cryopreservation media tested. A faster cooling rate of 1-2°C/min was significantly better than 0.5°C/min for all conditions tested, while rapid thawing at 37°C was not always superior to slow thawing at 4°C. Importantly, cryopreservation of mDA neural progenitor cells did not alter their potential to resume differentiation into mDA neurons. Banks of cryopreserved committed mDA neural progenitor cells provides a method to generate human dopaminergic neurons with reduced batch-to-batch variability, and establishes a mechanism to share lineage-primed cells for collaborative research.